Philips: blender / Nurul Izzah Yazid - Yazid, Nurul Izzah (2021)
Learning theories only give us small view but not how to deal with real situation. As a UiTM Perlis student, it is a part of study to do a case study project on purpose to research more about a product and other informations related. We deeply interested to learn more about Philips, an electronics retailer. Firstly, related general information has been collected through primary and secondary sources. Secondly, the report contains the specialized subject studies. The objective of this project is to learn more about the background, organizational structure, product and service provided. In this task, I have conducted a SWOT analysis of the product I chose. I have studied a product which was blender by a company named as Philips. Here, I will be sharing about the problems of Philips’s blender detected. The noticeable problems are prices that are not affordable for everyone, competing with other brands and the product has a noisy sound. Through this case study, I will be describing more deeper about the problems and alternatives solutions regarding the problem.